ANALISIS KOMPARATIF SISTEM PEMBUKTIAN KARTEL INDONESIA DAN MALAYSIA DI ERA MEA DALAM PERSPEKTIF HUKUM PERSAINGAN USAHA - Aswim, Danar (Sekolah Tinggi Ilmu Hukum Sumpah Pemuda, 2021)
The writing of this title is motivated by the inconsistency of cartel according to Law no. 5 year 1999, then the writer compares it with Competition Act 2010 to see conformity about cartel concept and its proof system. The writing of this law raised the problem of how the system of proof of cartel based on the nature of the ban according to Law no. 5 of 1999 and the Competition Act 2010 in Malaysia, as well as how the juridical implications of the differences and the nature of the cartel ban between Law no. 5 of 1999 and the 2010 Competition Act with respect to MEA. Law no. 5 of 1999 and the 2010 Competition Act, there are differences in the nature of the prohibition to prove the existence of indications of alleged monopolistic practice of cartel. The scope and nature of the prohibition of cartel causes legal uncertainty and the failure of the MEA objectives in the business competition law to strengthen a healthy competition culture.